Electrochemical Characterization of Vitreous Humor. (2017) - Silue, Tjerignimin A.; Mannikanti, Saugandhika; Peixoto, Nathalia
Abstract: The vitreous is a gel-like structure found in the eyes above the retina. We are interested in characterizing the vitreous electrochemically in order to help define safety measures for future retinal prostheses. Here we show results from characterization of vitreous in phosphate buffered saline (PBS), in thimerosal, and by itself. Our results showed that the the vitreous is resistive for a large frequency range. The electrochemical profile shows an increase in impedance modulus as thimerosal is added; the cathodic charge storage capacity of both the vitreous with and without thimerosal remained unchanged.